KNOWLEDGE, ATTITUDE, AND IMPLEMENTATION OF COLD CHAIN MANAGEMENT IN BOALEMO DISTRICT, GORONTALO, INDONESIA - Pangalo, Paulus; Sapiun, Zulfiayu; Ischak, Wenny Inno; Goi, Misrawatie; Hartati, Hartati (Journal of Health Policy and Management, 2020)
Background: Children's health is a priority in health development with the goal of reducing child mortality. So far, high immunization coverage does not guarantee the emergence of diseases that can be prevented by immunization (PD3I). Cold Chain Management is a system used to store vaccines in good condition which refers to the vaccine supply chain for the immunization procurement chain. The purpose of this study was to examine the relationship of knowledge, attitude, and implementation of cold chain management.Subjects and Method: This was a cross sectional study conducted at 11 health centers in Boalemo District, Gorontalo, Indonesia, in September 2018. A sample of 34 health officers was selected purposively. The dependent variable was cold chain management. The independent variables were knowledge and attitude. The data were collected by questionnaire and observation sheets. The data were analyzed by Chi square.Results: High knowledge increased positive attitude toward implementation of cold chain management (OR= 5.87; p= 0.061). High knowledge (OR= 2.17; p= 0.448) and positive attitude (OR= 2.69; p= 0.405) increased implementation of cold chain management, but they were statistically non-significant.Conclusion: High knowledge and positive attitude increase implementation of cold chain managementKeywords: cold chain management, vaccine, knowledge, attitudeCorrespondence: Zulfiayu Sapiun. Department of Pharmacy, Health Polytechnics, Ministry of Health Gorontalo.Jl. Taman Pendidikan 36, Gorontalo 96123, Indonesia. Email: zulfiayu@poltekkesorontalo.ac.id. Mobile: 081244521639Journal of Health Policy and Management (2020), 05(02): 139-145https://doi.org/10.26911/thejhpm.2020.05.02.06